2020
DOI: 10.1001/jamanetworkopen.2020.0708
|View full text |Cite
|
Sign up to set email alerts
|

Women’s Representation in Leadership Positions in Academic Medical Oncology, Radiation Oncology, and Surgical Oncology Programs

Abstract: IMPORTANCE Women are underrepresented in medical leadership positions; however, representation of women among academic oncology leadership is unknown. OBJECTIVES To evaluate representation of women overall and in leadership positions in academic medical oncology (MO), radiation oncology (RO), and surgical oncology (SO) programs and to examine the association of women leadership with overall faculty representation of women per program. DESIGN, SETTING, AND PARTICIPANTS In this cross-sectional study, MO, RO, and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

3
79
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 87 publications
(84 citation statements)
references
References 14 publications
3
79
0
Order By: Relevance
“… 5 Female participation at an educative level in oncology training programs and grand rounds seminars is also weaker, and is particularly pronounced at the leadership level. 6 , 7 With the proportion of female oncologists continuing to increase, it is essential that gender disparities be addressed.…”
Section: Introductionmentioning
confidence: 99%
“… 5 Female participation at an educative level in oncology training programs and grand rounds seminars is also weaker, and is particularly pronounced at the leadership level. 6 , 7 With the proportion of female oncologists continuing to increase, it is essential that gender disparities be addressed.…”
Section: Introductionmentioning
confidence: 99%
“…Despite near-parity in medical schools for decades, this has simply not materialized, raising concerns that the pipeline is not simply long but also leaky, with women dropping out of the pathway that leads to leadership in the field owing to gender-specific challenges. Prior studies have shown that women are paid less, 6 spend more time on parenting and domestic responsibilities, experience higher rates of burnout, 7 and face other challenges in reaching the leadership positions analyzed in the study by Chowdhary et al 1 Contributing factors include unconscious bias, the motherhood penalty, and lack of mentorship, among others. Recent studies have documented how these challenges play out within the field of oncology specifically.…”
mentioning
confidence: 99%
“…What should surprise us is the marked underrepresentation of women in more senior positions in medicine, even now, despite women's long-standing near-parity among medical school enrollees. The study by Chowdhary et al 1 adds to the increasing body of knowledge documenting this concerning fact with a comprehensive overview of gender distribution in the leadership of academic oncology programs in the United States, providing important benchmarking data for the field.…”
mentioning
confidence: 99%
See 2 more Smart Citations